2021
DOI: 10.3390/ma14092399
|View full text |Cite
|
Sign up to set email alerts
|

Water Sorption and Solubility of Flowable Giomers

Abstract: The objective of this study is the characterization of a novel experimental flowable giomer (G) regarding water sorption, water solubility, and the microstructural characteristics, in comparison to three commercial giomers: Beautifil flow Plus X F00 (B-F00), Beautifil flow F02 (B-F02) and Beautifil flow Plus X F03 (B-F03), Shofu, Kyoto, Japan. Methods: Water sorption/solubility was performed by weighing the specimens before and after water immersion for 1, 2, 3, 14, 21 and 30 days. Data analysis was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this study, all groups in Omnichroma except Cola 5000 and Essentia DW 2500 revealed -ve solubility values considering the possibility of incomplete dehydration of the materials, these negative values may be indicative of a low level of solubility rather than the complete absence of dissolution. These negative values have been explained by possible hydrolytic chemical reactions that result in the formation of hydroxides on the filler surface (Rusnac et al 2021). In other studies, it has been suggested that negative values may be the result of hydrogen bonds connecting the absorbed water molecules to polar groups of the polymer chains, which cannot be removed entirely (Tugba & Gonulol.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all groups in Omnichroma except Cola 5000 and Essentia DW 2500 revealed -ve solubility values considering the possibility of incomplete dehydration of the materials, these negative values may be indicative of a low level of solubility rather than the complete absence of dissolution. These negative values have been explained by possible hydrolytic chemical reactions that result in the formation of hydroxides on the filler surface (Rusnac et al 2021). In other studies, it has been suggested that negative values may be the result of hydrogen bonds connecting the absorbed water molecules to polar groups of the polymer chains, which cannot be removed entirely (Tugba & Gonulol.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of residual monomers released by the investigated materials were determined at 30 days, after performing the sorbtion and solubility test [13].…”
Section: Hplc Determination Of Residual Monomersmentioning
confidence: 99%
“…To the best of our knowledge, very few references are available in literature regarding these materials [11][12][13]. Giomers were characterized regarding optical properties, translucency and masking capacity [12], water sorption and solubility [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has a total filler content of 67.3 wt% (47.0 vol%) 25 and combines efficient flowable delivery with the strength, durability, and esthetics of “hybrid” composite materials. Furthermore, Beautifil Flow Plus F00's high compressive and flexural strength (350 MPa) make it clinically acceptable for both anterior and posterior class I–V lesions, including all anatomical details such as cusps and marginal ridges 26 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Beautifil Flow Plus F00's high compressive and flexural strength (350 MPa) make it clinically acceptable for both anterior and posterior class I-V lesions, including all anatomical details such as cusps and marginal ridges. 26 Both Beautifil II and Beautifil Flow Plus F00 utilize S-PRG technology and exhibit various properties that provide resistance to caries such as antibacterial activity, 22 inhibition of enamel demineralization, 23 multi-ion release, 27 and more. An important distinction between conventional and flowable giomer is that increased flow results in an increase in fluoride-release of the material.…”
mentioning
confidence: 99%